The Euclidean Distance Approach to Continuous Utility Functions - Mehta, G. (Quarterly Journal of Economics, 1991)
Journal Article The Euclidean Distance Approach to Continuous Utility Functions Get access Ghanshyam Mehta Ghanshyam Mehta University of Queensland, Australia Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 106, Issue 3, August 1991, Pages 975–977, https://doi.org/10.2307/2937938 Published: 01 August 1991